Efficacy of Cognitive Rehabilitation in Alzheimer Disease: A 1-Year Follow-Up Study. (January 2019) - Germain, Sophie; Wojtasik, Vinciane; Lekeu, Françoise; Quittre, Anne; Olivier, Catherine; Godichard, Vinciane; Salmon, Eric
Introduction: The benefit of cognitive rehabilitation (CR) for patients with early-stage Alzheimer disease (AD) remains difficult to assess. Method: An observational, prospective study was conducted in a sample of 52 patients with AD included in a clinical, individualized CR program. Cognitive rehabilitation consisted of 1 weekly session during 3 months at home, followed by 1 monthly contact for 9 months. Rehabilitation techniques were used by experienced therapists to adapt activities important for the patient. Evaluation of patient's dependence in activities and objective and subjective caregiver's burden was performed with a research quantitative scale immediately after the intervention and at 6-month and 1-year follow-up. Results: Analyses with repeated measure analysis of variance showed decreased patient's dependence for adapted activities at 3 months, 6 months, and 1 year. Objective and subjective percentage of caregiver's burden was also decreased at all evaluations with our research functional scale, while there was no change on Zarit's burden scale. Global cognition slightly decreased over 1 year. Conclusions: This observational study in a clinical setting is in line with the benefit of CR for patients with mild AD reported in recent randomized controlled trials. The benefit obtained for adapted activities remained after 1 year, even if global cognition declined. Moreover caregiver's burden related to all individually relevant daily activities (from a list of 98) evaluated within the CR program was decreased after 1 year. Those preliminary results emphasize the importance of choice for the measurement instrument to report CR efficacy and claim for further validation of such tools.